Rhythm pattern discovery in Niger-Congo story-telling - Gibbon, Dafydd (Frontiers in Communication, 2023)
Description of interactive oral story-telling in West African Niger-Congo languages, “orature” in contrast to “literature”, has traditionally been firmly in the domain of anthropological linguistics. The discourse structures of narrator-responder interaction and call-response chanted interludes and their prosody are an open challenge to discourse analysts, linguists and phoneticians. Two orature examples from related Niger-Congo languages, recorded during fieldwork in Côte d'Ivoire, are analyzed from a macrostructural acoustic phonetic perspective in terms of realtime rhythms, and then compared with other related orature examples and examples of reading aloud. In this transdisciplinary methodology, long time domains of up to 5 min in duration and beyond are studied using long-term spectra and spectrograms of the amplitude modulation of speech. Long-distance timing regularities and their variation during story-telling exchanges are analyzed in detail and explained in terms of Rhythm Formant Theory (RFT), a further development of Speech Modulation Theory, and its associated methodology Rhythm Formant Analysis (RFA).